The application of institutional research in a senior high school of Taiwan - SHUFANG LIN; YIH-JENG LIN (Journal of Advanced Research in Social Sciences and Humanities, 2016)
Aim: To support student recruitment policies and school management strategies with data-driven decisions, the author of this paper conducted an experiment using Institutional Research (IR).Method: In this investigation, the